Disc-mass distribution in star-disc encounters - Steinhausen, Manuel; Olczak, Christoph; Pfalzner, Susanne (Astronomy and astrophysics, 2012)
Aims: Investigations of stellar encounters in cluster environments have demonstrated their potential influence on the mass and angular momentum of protoplanetary discs around young stars. We investigated how far the initial surface density in the disc surrounding a young star influences the outcome of an encounter. Methods: The numerical method applied here allows us to determine the mass and angular momentum losses in an encounter for any initial disc-mass distribution. On the basis of a power-law ansatz for the surface density, Σ(r) ∝ r−p, we perform a parameter study of star-disc encounters with different initial disc-mass distributions using N-body simulations. Results: We demonstrate that the shape of the disc-mass distribution has a significant impact on the quantity of the disc-mass and angular momentum losses in star-disc encounters. In particular, the results are most sensitive to how the outer parts of the disc are perturbed by high-mass stars. In contrast, disc-penetrating encounters lead more or less independently of the disc-mass distribution always to large losses. However, maximum losses are generally obtained for initially flat distributed disc material. Based on a parameter study, a fit formula is derived, describing how the relative mass and angular momentum loss depend on the initial disc-mass distribution index p. Encounters generally lead to a steepening of the density profile of the disc. The resulting profiles can have a r-2-dependence or an even steeper one that is independent of the initial distribution of the disc material. Conclusions: From observations, the initial density distribution in discs remains unconstrained, hence the strong dependence on the initial density distribution that we find here might require a revision of the effect of encounters in young stellar clusters. The steep surface density distributions induced by some encounters might be a prerequisite to the formation of planetary systems similar to our own Solar System.